# How can I evaluate ${lim_{hto 0}frac{cos(pi + h) + 1}{h}}$?

Mathematics Asked by DCdaKING on January 7, 2022

I’m supposed to evaluate the following limit using the cosine of a sum and one of the "special limits" which are $${lim_{xto 0}frac{sin(x)}{x}=1}$$ and $${lim_{xto 0}frac{1-cos(x)}{x}=0}$$.

The limit is : $${lim_{hto 0}frac{cos(pi + h) + 1}{h}}$$

I currently have : $${frac{cos(pi)cos(h) – sin(pi)sin(h) + 1}{h}}$$

I’m not sure where to go from here and have been stuck for awhile, help would be very much appreciated.

The hint was given to you:

$$lim_{hto0}frac{cos(pi+h)+1}h=lim_{hto0}frac{cospicos h-sinpisin h+1}h=lim_{hto0}frac{1-cos h}h=0.$$

Answered by user65203 on January 7, 2022

This is actually asking you the derivative of $$cos(x)$$ at $$x=pi$$.

We can rewrite the expression as: $$lim_{hrightarrow0}frac{cos(pi+h)-cos(pi)}{pi+h-pi}longrightarrow cos^prime(pi)$$ The derivative of $$f(x)$$ refers to $$lim_{hlongrightarrow0}frac{f(x+h)-f(x)}{x+h-x}$$

If you know derivative, you know that $$cos^prime(pi)=-sin(pi)=0$$

I am not sure if this problem is designed to be solved this way, but it reminds me a problem I did before, and that problem is solved this way.

Answered by Henry L on January 7, 2022

Since $$cos(pi)=-1$$ and $$sin(pi) =0$$ we have: $$frac{cos(pi)cos(h) - sin(pi)sin(h)+1}{h} = frac{-cos(h)+1}{h} = frac{1-cos(h)}{h}$$

Answered by azif00 on January 7, 2022

You have written it correctly. Now because $${sin(pi)=0}$$ and $${cos(pi)=-1}$$ it simplifies further to

$${frac{cos(pi)cos(h) - sin(pi)sin(h) + 1}{h}=frac{-1times cos(h) - 0times sin(h)+1}{h}=frac{-cos(h) + 1}{h}}$$

can you take it from here?

Answered by Riemann'sPointyNose on January 7, 2022

Get help from others!